Percy Jackson’s Eco-Hero’s Journey through Greek Mythology in Rick Riordan’s The Lightning Thief - Wardana, Bezaliel Oliver (Universitas Negeri Surabaya, 2025)
The Lightning Thief (2005) by Rick Riordan is a famous children/juvenile’s novel following a demigod boy named Percy Jackson in modern day America, which recently got a TV show adaptation by Disney. The purpose of the research is to find out how Percy Jackson becomes an eco-hero. The research archetypal criticism to find narrations, monologues, dialogues, words, and phrases to analyze the context and mythological aspect used to aid in telling Percy Jackson’s journey to become an eco-hero. The research uses Christopher Vogler’s character archetypes to organize each character’s role in the story that have a role in Percy Jackson’s eco-hero’s journey, and stages of the journey to map out Percy Jackson’s journey to become an eco-hero. Through close reading and textual analysis, the research found due to the intended children/juvenile audience of the book, the implementation of environmental and nature aspects in the story is done by first establishing Percy Jackson’s connection and interactions with water and nature through the use of the persistent and vast Greek mythology’s archetypal nature and many nature-related aspects to create indirect ways to showcase Percy Jackson’s hero’s journey to become an eco-hero so as to not bog down the narrative nor distract the audience so they can be invested in the story.